2013
DOI: 10.1227/neu.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Transferring a Motor Branch of the Tibial Nerve to the Deep Peroneal Nerve for Treatment of Foot Drop

Abstract: The transfer of the nerve of the soleus muscle to the deep peroneal nerve demonstrated poor results in most of the patients, although favorable outcomes were observed in a few subjects. Due to the inconsistency of the results, we do not favor the routine use of this technique for the treatment of foot drop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…All included studies were retrospective case series published between 2008 and 2015. 1,2,15,16 The mean modified NOS score for the included studies was 5.0/6.0. [20][21][22]…”
Section: Study Selection Quality Assessment and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included studies were retrospective case series published between 2008 and 2015. 1,2,15,16 The mean modified NOS score for the included studies was 5.0/6.0. [20][21][22]…”
Section: Study Selection Quality Assessment and Study Characteristicsmentioning
confidence: 99%
“…Consequently, there has been considerable variability in the reported outcomes with the use of nerve transfers in peroneal nerve palsy. 1,2,[13][14][15][16][17] The objective of this work was to perform a systematic review and meta-analysis of the primary literature to assess the effectiveness of nerve transfer surgery in restoring ankle dorsiflexion in patients with peroneal nerve palsy.…”
mentioning
confidence: 99%
“…The limited clinical outcome literature to date has shown inconsistent outcomes after tibial nerve transfer for tibialis anterior reanimation in adult patients and are summarized in Table . When considering partial tibial nerve transfers to the deep peroneal nerve, excellent results were reported by Nath et al (), where good outcomes (≥M4 grading of ankle dorsiflexion) were achieved in 7 of 9 patients, but Flores et al () described frustratingly poor results with only 1 of 10 of patients achieving a good outcome. In regards to partial tibial nerve transfers to the motor branches of tibialis anterior, which is the procedure described in this study, Giuffre et al () also described poor results with only 1 of 11 patients achieving a good outcome.…”
Section: Discussionmentioning
confidence: 96%
“…In regards to partial tibial nerve transfers to the motor branches of tibialis anterior, which is the procedure described in this study, Giuffre et al () also described poor results with only 1 of 11 patients achieving a good outcome. No authors reported any significant functional donor nerve deficit (Flores, Martins, & Siqueira, ; Giuffre, Bishop, Spinner, Levy, & Shin, ; Nath, Lyons, & Paizi, ). A more recent study by Leclère et al () also utilizing the partial tibial nerve transfer to motor branches of tibialis anterior demonstrated ≥M4 ankle dorsiflexion in 3 of 6 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation